Pengembangan LKPD Berorientasi Pendekatan Saintifik dengan Aplikasi Liveworksheet Untuk Siswa Kelas IV Sekolah Dasar - Nanda Retno Wulandari; Kukuh Andri Aka; Bagus Amirul Mukmin (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2023)
This research is motivated by observations which show that the Student Worksheets (LKPD) in elementary schools have not been varied and are still print-based so they cannot accommodate the role of technology. LKPD is still in the form of multiple choice questions and descriptions so it is less interesting for students. The purpose of this study was to determine the validity, practicality and effectiveness of the scientific approach-oriented worksheets with live worksheet applications for fourth grade elementary school students so that they are feasible to use and improve student activities and learning outcomes. The research method used is R&D (Research and Development) research with the ADDIE model which includes the analysis, design, development, implementation, and evaluation stages. The research subjects were teachers and fourth grade students of MI Jumog, Trenggalek Regency. The results of this study are (1) the validity of obtaining results 82% from material experts, 90% from construction experts and 93% from linguists, (2) practicality getting 96% percentage of teacher responses and 96% of student responses, and (3 ) the effectiveness of obtaining the percentage of classical learning completeness (KBK) is 88%. Thus, it can be concluded that the LKPD oriented to a scientific approach with the application of the live worksheet theme 2 sub-theme 2 is declared valid, practical and effective to support fourth grade learning in elementary schools